Effects of Once-a-week Interval Training Based on Body Mass Index and Exercise Frequency - Yonghwan Kim; Haemi Jee (Asian Society of Kinesiology, 2018)
PURPOSE The purpose of this study was to analyze the effects of exercise habit and body mass index(BMI) on once-a-week high intensity interval training (HIIT) in young females. 30 college-aged participants conducted a 60-minute exercise program for 12 weeks. METHODS Questionnaires on exercise habit, body composition analysis, physical fitness tests were conducted before and after 12 weeks. The training intensity was set to peak HR of 85% or more, and the program consisted muscular strengthening exercises using weight training tools, props, and a gymball. Time of exercise and rest between exercises were both 30 seconds. Participants were divided by BMI(lower BMI(n=15) and higher BMI(n=15)) and the groups were further divided into the lower and higher activity groups by the number of regularly performed exercise days per week(lower -activity(n=17) 0-2 days and higher-activity(n=13) =3 days. RESULTS As results, the lower BMI group showed a significant reduction in BMI(kg/m2) and the higher BMI group showed significant improvements in all body components including BMI(kg/m2), body fat(%), and percent body fat(%) after the intervention. In the case of physical fitness changes based on lower and higher BMI, both groups showed significant improvements in grip strength(kg), vertical jump(cm), and squat(sec). As for exercise frequency, BMI, body fat and body fat percentage were significantly decreased, and the muscle percentage was significantly increased in the higher-activity group. In the lower-activity group, body weight and BMI decreased significantly. CONCLUSIONS In conclusion, young healthy females with higher BMI and activity level tend to show greater changes in body composition and physical fitness level.